2004
DOI: 10.1207/s15327914nc5001_4
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Colorectal Cancer Mortality: Results From the Japan Collaborative Cohort Study

Abstract: The relationship between diet and colorectal cancer mortality was analyzed in a prospective study of 45,181 men and 62,643 women aged 40-79 yr enrolled in the Japan Collaborative Cohort Study. Between 1988 and 1990, sub-jects completed a self-administered questionnaire on their sociodemographic characteristics, diet, and other lifestyle habits. During the follow-up period (average 9.9 yr), 284 colon cancer deaths (138 men and 146 women) and 173 rectal cancer deaths (116 men and 57 women) were confirmed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 30 publications
2
84
2
2
Order By: Relevance
“…In western countries, some studies have shown that high intake of meat may increase the risk of colorectal cancer (Larsson et al, 2005;Norat et al, 2005). However, some studies in Japan did not show clear associations between colorectal cancer, colon cancer and rectal cancer (Kojima et al, 2004;Sato et al, 2006). Similar to studies in Japan, the mean intake of meat did not differ between cases and controls.…”
Section: Discussionsupporting
confidence: 57%
“…In western countries, some studies have shown that high intake of meat may increase the risk of colorectal cancer (Larsson et al, 2005;Norat et al, 2005). However, some studies in Japan did not show clear associations between colorectal cancer, colon cancer and rectal cancer (Kojima et al, 2004;Sato et al, 2006). Similar to studies in Japan, the mean intake of meat did not differ between cases and controls.…”
Section: Discussionsupporting
confidence: 57%
“…Walters et al concluded that high cruciferous vegetable intake might decrease colorectal cancer risk by enhancing the elimination of PhIP and related dietary heterocyclic amine carcinogens. Although a number of case-control studies conducted prior to 1990 found that people diagnosed with colorectal cancer were more likely to have lower intakes of various cruciferous vegetables than people without colorectal cancer [19][20][21][22], most prospective cohort studies have not found significant inverse associations between cruciferous vegetable intake and the risk of developing colorectal cancer over time [23][24][25][26]. One exception was a prospective study of Dutch adults, which found that men and women with the highest intakes of cruciferous vegetables (averaging 58 g/d) were significantly less likely to develop colon cancer than those with the lowest intakes (averaging 11 g/d) [27].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…In some, no association was observed (4), whereas in others a strong association was seen (5,6). Recent results from seven cohort studies (7)(8)(9)(10)(11)(12)(13) only partly confirm a modest association with red meat (including processed meat in most cases; refs. [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12]. Virtually, all cohort studies found an increased risk for colon cancer with processed meat consumption (2,(7)(8)(9)(10)(11)(12). Results for rectal cancer were inconsistent.…”
Section: Introductionmentioning
confidence: 99%